Record of Convolvulus crenatifolius Ruiz & Pavón (Convolvulaceae) in Mexico - Carranza González, Eleazar (Instituto de Ecología, A.C., 2005)
Convolvulus crenatifolius Ruiz & Pavón is reported from Mexico for the first time. This species is native to South America. However, since as early as the end of the 19th century, it has been collected various times in central Mexico where it occurs in disturbed areas and is presumably adventitious. A morphological description is provided, as well as a key to separate this species from C. bonariensis Cav. and C. equitans Benth., two similar taxa with which C. crenatifolius is related.